A Conceptual Model to Assess the Impact of Quality Management Systems on the In-Vitro Diagnostics Industry in South Africa - Stoltz, J. C.; Govender, Krishna K. (International Review of Management and Marketing, 2023)
Although ISO certification has become compulsory, it is unclear what impact ISO certification has on the South African medical device industry and how the forced ISO certification will affect individual companies and the industry with regard to the quality of products and service delivery. Furthermore, no research to date has been performed specifically on the contribution or impact of ISO certification in the IVD industry in South Africa. Through an in-depth synthesis of published research, and by triangulating the literature on quality in the medical domain, the researchers have conceptualized possible relationships between various quality constructs and ISO quality certification with respect to in-vitro diagnostics. This conceptual study will contribute specifically to the South African IVD market and possibly other IVD markets worldwide to understand how certification issues will impact quality, customer service, operations, and performance.